The Effect of Community Integration and General Satisfaction to Loyalty - Reny Nurhayati (Business and Entrepreneurial Review, 2007)
The background of this research was, loyalty is a key marketing goal is so widely accepted that its value has been deemed to be "self-evidence to every business person". With such importance, it is not surprising that loyalty is the focus of a significant body of literature in marketing. Within that literature, marketers have generally share a fundamental understanding of what loyalty means and how it is created. Loyalty has been traditionally understoot do be reflected by repeat purchase behavior and/orthe expression of a favorable attitude toward such behavior. Research device, used in research, is descriptive research device where using the method of analysis of regression. With amount of sample counted from 100 customers Kelapa Gading Mall Jakarta. From the result of this research finding contribute to marketing theory and have implications for marketing practice. With regard theory, we provide additional evidence that the accumulation of consumption experience among customer that express a willingness other forces, in this case brand community integration, become more powerful in building loyalty than prior research, provides a strong challenge to conventional understanding regarding the antecedents the loyalty.